FUNGSI MEDIASI PADA PROSES PERCERAIAN PNS DI LINGKUNGAN PEMERINTAH KABUPATEN TANA TIDUNG - Lamadokend, Juliana Somibeda (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of living a perfect, happy and eternal life. In reality, not all marriages go as expected, resulting in divorce. This research aims to analyze personnel policies in fostering household harmony and supporting improved employee performance, factors causing civil servant divorce, the mediation process carried out by BKPSDM, analyzing obstacles and solutions in conducting mediation in the civil servant divorce process within the Tana Tidung Regency Government. This research uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The results of the research show that the Tana Tidung Regency government's policy in fostering employee household harmony is carried out through religious activities, providing leave, counseling guidance, socialization regarding household harmony. Factors that cause civil servant divorce include infidelity, economics, differences in principles, ideology and religion. In the civil servant divorce application process, BKPSDM plays the role of mediator. The obstacles faced were one of the parties being unable to attend, the parties not being cooperative, unable to accept suggestions and incomplete administrative requirements. The solution is to write a summons to the parties involved, invite other parties to obtain additional information and contact employees to complete the requirements for applying for a divorce permit so that the next process can be carried out.